2007
DOI: 10.1007/s11097-007-9066-y
|View full text |Cite
|
Sign up to set email alerts
|

Intuitions about consciousness: Experimental studies

Abstract: When people are trying to determine whether an entity is capable of having certain kinds of mental states, they can think of it either from a functional standpoint or from a physical standpoint. We conducted a series of studies to determine how each of these standpoints impact people's mental state ascriptions. The results point to a striking difference between two kinds of states-those that involve phenomenal consciousness and those that do not. Specifically, it appears that ascriptions of states that involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(193 citation statements)
references
References 18 publications
8
185
0
Order By: Relevance
“…Functionalism is preferred by most collectivists today since it enables one to argue for collectivism without having to make unpalatable dualistic or emergentist ontological commitments. But it is debatable whether folk metaphysics of agency and of the mind is really functionalist (see Knobe and Prinz 2008).…”
Section: Fundingmentioning
confidence: 99%
“…Functionalism is preferred by most collectivists today since it enables one to argue for collectivism without having to make unpalatable dualistic or emergentist ontological commitments. But it is debatable whether folk metaphysics of agency and of the mind is really functionalist (see Knobe and Prinz 2008).…”
Section: Fundingmentioning
confidence: 99%
“…As shown in Figure 2, Huebner found that while participants tended to treat the human and the robot similarly with regard to the nonphenomenal states (they were generally willing to attribute belief to both the human and the robot), they tended to treat the human and the robot dissimilarly with regard to the phenomenal states (they were generally willing to attribute both pain and happiness to the human, but not the robot). Huebner notes that at first glance, his results might appear to support the view advanced by Knobe and Prinz (2008), in that they "seem to confirm that commonsense psychology does draw a distinction between phenomenal and non-phenomenal states-and this distinction seems to be dependent on the structural properties of an entity in a way that ascriptions of non-phenomenal states are not" (138-139). He goes on to argue that to move from his results to such a conclusion is to move far too quickly, however.…”
Section: Related Findingsmentioning
confidence: 87%
“…Results of Study 2 in Knobe and Prinz (2008), showing the mean response for each sentence in descending order (1= "sounds weird" and 7="sounds natural").…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations